2021
DOI: 10.1177/03000605211044364
|View full text |Cite
|
Sign up to set email alerts
|

Use of a new set of key performance indicators for evaluating the performance of an in vitro fertilization laboratory in which blastocyst culture and the freeze-all strategy are the primary treatment in patients with in vitro fertilization

Abstract: Objective To evaluate the performance of an in vitro fertilization (IVF) laboratory using a new set of key performance indicators (KPIs) when the main treatment of IVF patients had been changed. Methods Patients who underwent fresh embryo transfer and the freeze-all strategy in August, September, and October 2017 were retrospectively studied to evaluate the performance of an IVF laboratory in September when implantation rate of fresh embryo transfer decreased. KPIs associated with blastocyst culture and the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Therefore, it is standard procedure to reject these embryos after a fertilization check. When we assessed the studies published by Pirea et al , Variaelli et al , Zaca et al , Hammond et al , and Wang et al [9,10,11 ▪▪ ,15,16], we concluded that polyspermy rate was not considered an important KPI when compared to other evaluated PIs. Although many publications do not mention the number of PNs as a PI should be considered, as also mentioned in the Vienna Consensus, it can provide a marker of a problem in gamete handling or culture conditions and should be low under normal conditions.…”
Section: Technical Key Performance Indicators In Embryology Labmentioning
confidence: 89%
“…Therefore, it is standard procedure to reject these embryos after a fertilization check. When we assessed the studies published by Pirea et al , Variaelli et al , Zaca et al , Hammond et al , and Wang et al [9,10,11 ▪▪ ,15,16], we concluded that polyspermy rate was not considered an important KPI when compared to other evaluated PIs. Although many publications do not mention the number of PNs as a PI should be considered, as also mentioned in the Vienna Consensus, it can provide a marker of a problem in gamete handling or culture conditions and should be low under normal conditions.…”
Section: Technical Key Performance Indicators In Embryology Labmentioning
confidence: 89%
“…This study provides overviews of current practice and important standards for creating KPIs. All 14 KPIs have benchmarks available [12].…”
Section: Types Of Artmentioning
confidence: 99%